The Influence of Adolescent Social Environment on Religious Identity Crisis Among Students of The Islamic Religious Education Study Program - Niswatul Azizah; Indria Nur; Khatipah Khatipah (Hikmah, 2026)
Religious identity crisis among university students has become an increasingly relevant issue amid the complexity of contemporary social dynamics and diverse social influences. This study aimed to examine the effect of the social environment on religious identity crisis among students of the Islamic Religious Education Program at IAIN Sorong. A quantitative correlational design was employed. The study population consisted of 218 students, while the sample size was determined using the Yamane formula, resulting in 69 respondents. However, 75 valid questionnaires were collected and included in the analysis. Data were gathered through questionnaires measuring social environment and religious identity crisis variables. Statistical analyses included normality testing, linearity testing, simple linear regression, and coefficient of determination analysis. The findings revealed a significant effect of the social environment on students’ religious identity crisis, with a significance value of 0.000 (p < 0.05). The regression equation (Y = 79.264 − 0.662X) indicated a negative relationship between the variables. Furthermore, the coefficient of determination (R² = 0.717) showed that the social environment explained 71.7% of the variance in religious identity crisis, highlighting its substantial role in shaping students’ religious identity development.